2021
DOI: 10.37929/nveo.817562
|View full text |Cite
|
Sign up to set email alerts
|

Spathulenol as the most abundant component of essential oil of Moluccella aucheri (Boiss.) Scheen

Abstract: The genus Moluccella (Lamiaceae) encompasses eight species among which Moluccella aucheri (Boiss.) Scheen and M. laevis L. are available in Iran. The aim of this study is characterizing the essential oil of dried aerial parts of M. aucheri collected from the South of Iran. The essential oil was hydrodistilled and then analysed by GC-MS. Twenty-one compounds were identified in the oil of M. aucheri. The most abundant components of the oil were an aromadendrane sesquiterpene; spathulenol (63.3%) together with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…(+)Spathulenol is used in the production of environmentally friendly insecticides against cereal pests. [40] (+)Spathulenol also has anticholinesterase, [41,42] antinociceptive, anti-hyperalgesic, [42,43] anti-micobacterial, [42,44,45] antioxidant, anti-proliferative, anti-oedematogenic, [42,45] cytotoxicity, [42,46] and is used as a chemotherapy adjuvant for MDR cancer. [42,47] While cis-lanceol was represented in S. lappa and L. sinensis (0.46 % and 0.24 %, respectively).…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 99%
“…(+)Spathulenol is used in the production of environmentally friendly insecticides against cereal pests. [40] (+)Spathulenol also has anticholinesterase, [41,42] antinociceptive, anti-hyperalgesic, [42,43] anti-micobacterial, [42,44,45] antioxidant, anti-proliferative, anti-oedematogenic, [42,45] cytotoxicity, [42,46] and is used as a chemotherapy adjuvant for MDR cancer. [42,47] While cis-lanceol was represented in S. lappa and L. sinensis (0.46 % and 0.24 %, respectively).…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 99%
“…It also plays significant roles in pathophysiologic processes like oxidative stress, thymidine incorporation in to DNA and inflammation [37]. Spathulenol (another abundant compound in the leaves EO of C. adenocaule), is a tricyclic sesquiterpene with 5,10-cycloaromadendrane skeleton [44]. Literature surveys revealed that spathulenol possess significant biological applications such as antihyperalgesic, antioxidant, anticholinesterase, antibacterial, antiproliferative, antiinflammatory, antioedematogenic, chemotherapy of MDR cancer and cytotoxicity [39].…”
Section: Antibacterial Activitiesmentioning
confidence: 99%